2016
DOI: 10.4055/cios.2016.8.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Lateral Unicompartmental Knee Arthroplasty: Minimum 2-Year Follow-up

Abstract: BackgroundWe investigated the clinical results and early complications after lateral unicompartmental knee arthroplasty (UKA) using the Zimmer unicompartmental high-flex knee (ZUK) prosthesis with a minimum follow-up of 2 years.MethodsTwenty-seven patients (30 cases) who underwent lateral UKA with the ZUK prosthesis between January 2011 and February 2014 were selected for this study. The mean age of the patients was 63.3 years at the time of surgery, and the mean followup was 3 years and 2 months (range, 24 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…Data from 32 studies were available to compare mobile-bearing vs. fixed-bearing implants; 10 studies (n ¼ 2,268) with mobile-bearing implants [14,18,28,32,33,37,38,41,50,53], 18 studies (n ¼ 1,469) with fixed-bearing [8,26,[42][43][44][45][46][47][48][49]27,30,31,[34][35][36]39,40] and 4 additional studies that reported outcomes for both (n ¼ 1,743 mobile-bearing, n ¼ 790 fixed-bearing) [25,29,46,51]. 18 studies had a moderate risk of bias [8,18,[44][45][46][47][48][49][50]53,26,31,33,34,37,39,42,…”
Section: Fixed-vs Mobile-bearing Componentsmentioning
confidence: 99%
“…Data from 32 studies were available to compare mobile-bearing vs. fixed-bearing implants; 10 studies (n ¼ 2,268) with mobile-bearing implants [14,18,28,32,33,37,38,41,50,53], 18 studies (n ¼ 1,469) with fixed-bearing [8,26,[42][43][44][45][46][47][48][49]27,30,31,[34][35][36]39,40] and 4 additional studies that reported outcomes for both (n ¼ 1,743 mobile-bearing, n ¼ 790 fixed-bearing) [25,29,46,51]. 18 studies had a moderate risk of bias [8,18,[44][45][46][47][48][49][50]53,26,31,33,34,37,39,42,…”
Section: Fixed-vs Mobile-bearing Componentsmentioning
confidence: 99%
“…To date, there are only few published reports on the clinical outcome and survivorship of fixed-bearing lateral UKR with large variability in clinical results and longevity [ 17 , 18 , 29 35 ]. The primary objective of this study was to assess the clinical effectiveness of the FLO partial knee replacement in a large cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this technique lie in the low loss of blood during the operation and a low rate of complications. [37,38] The results of medial and lateral partial arthroplasty are similar. Partial arthroplasty is contraindicated in patients with involvement of other compartments of the knee, presence of instability, inflammatory arthritis, and fixed valgus deformity.…”
Section: Table 2: Advantages and Disadvantages Of Arthroscopy And Osteotomy At The Same Timementioning
confidence: 81%